CON4EI: Short Time Exposure (STE) test method for hazard identification and labelling of eye irritating chemicals. (June 2018) - Adriaens, E.; Willoughby, J.A.; Meyer, B.R.; Blakeman, L.C.; Alépée, N.; Fochtman, P.; Guest, R.; Kandarova, H.; Verstraelen, S.; Van Rompay, A.R.
Abstract: Assessment of ocular irritancy is an international regulatory requirement in the safety evaluation of industrial and consumer products. Although many in vitro ocular irritation assays exist, alone they are incapable of fully categorizing chemicals. Therefore, the CEFIC-LRI-AIMT6-VITO CON4EI consortium was developed to assess the reliability of eight in vitro test methods and establish an optimal tiered-testing strategy. One assay selected was the Short Time Exposure (STE) assay. This assay measures the viability of SIRC rabbit corneal cells after 5 min exposure to 5% and 0.05% solutions of test material, and is capable of categorizing of Category 1 and No Category chemicals. The accuracy of the STE test method to identify Cat 1 chemicals was 61.3% with 23.7% sensitivity and 95.2% specificity. If non-soluble chemicals and unqualified results were excluded, the performance to identify Cat 1 chemicals remained similar (accuracy 62.2% with 22.7% sensitivity and 100% specificity). The accuracy of the STE test method to identify No Cat chemicals was 72.5% with 66.2% sensitivity and 100% specificity. Excluding highly volatile chemicals, non-surfactant solids and non-qualified results resulted in an important improvement of the performance of the STE test method (accuracy 96.2% with 81.8% sensitivity and 100% specificity). Furthermore, it seems that solids are more difficult to test in the STE, 71.4% of the solids resulted in unqualified results (solubility issues and/or high variation between independent runs) whereas for liquids 13.2% of the results were not qualified, supporting the restriction of the test method regarding the testing of solids. Highlights: CON4EI: CONsortium for in vitro Eye Irritation testing strategy (TS). 80 reference chemicals tested with the Slug Mucosal Irritation (SMI) test. Eye damaging/Eye irritation potency predcited by amount of mucus produced. The SMI test method correctly identified 65.8% of the Cat 1 chemicals. Low over-prediction rate for in vivo Cat 2 and No Cat chemicals.